Construction and validation of a non- verbal test to measure some science concepts among preschoolers - Malaga, Irene G. (1977)
In this study, the researcher constructed and evaluated a 30-item test to measure some sciene concepts among preschoolers. For editing as well as for checking the items were presented to some co-MAT participants and to a science specialist. An informal interview with some preschoolers was conducted to ensure that the options were what the illustrations represented.
"March, 1977."
Thesis (M.A.T. Elementary Science)--University of the Philippines, Diliman.
Keywords: Life sciences -- Study and teaching (Preschool) -- Philippines -- Oton (Iloilo); Preschool children -- Philippines -- Oton (Iloilo)